2021
DOI: 10.3390/en14113233
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Energy Poverty of Polish Students during the COVID-19 Pandemic

Abstract: The aim of this paper is to define the factors influencing the level of energy poverty among students. The analysis of these factors is based on the results of a survey conducted among a group of 937 students at the Cracow University of Economics. The study takes into consideration the changes in the attitudes and behavior of students resulting from the introduction of distance learning during the COVID-19 pandemic. The switch to distance learning resulted in a significant increase in the number of responses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…It can be concluded that the level of energy poverty in the country has increased and the most affected have been the low-income households. Similar results were obtained in the research by Mamica et al [109]. The authors analyzed the factors influencing energy poverty among Polish students during the pandemic.…”
Section: Impact On Energy Poverty Of Householdssupporting
confidence: 85%
“…It can be concluded that the level of energy poverty in the country has increased and the most affected have been the low-income households. Similar results were obtained in the research by Mamica et al [109]. The authors analyzed the factors influencing energy poverty among Polish students during the pandemic.…”
Section: Impact On Energy Poverty Of Householdssupporting
confidence: 85%
“…A set of indicators should be used to assess energy poverty as each can reflect a different aspect of the phenomenon. The measurement can be based on both objective and subjective measures [35]. Their interpretation should be carried out jointly.…”
Section: Energy Poverty-definition Measurement and Indicatorsmentioning
confidence: 99%
“…Kousis et al (2020) collected and analyzed data from students living in the private-rented sector from Bulgaria, Cyprus, Greece, Lithuania, Romania, the UK, and Ireland, focusing on the impact of the characteristics of students' houses on their energy bills, thermal comfort, and wellbeing. In the study of Mamica et al (2021), the objective was to define the factors influencing the level of EP among Polish students, considering the changes in their attitudes and behavior resulting from the introduction of distance learning during the COVID-19 pandemic. Nazarahari et al (2021) compared the attitudes of Japanese and non-Japanese college students, who lived in private or shared accommodations, toward energy usage and the impact of the high cost of energy on their use and saving practices.…”
Section: Introductionmentioning
confidence: 99%